A simple energy-based strategy for sensor orientation in borehole microseismic monitoring - Lagos, Soledad Rocío (2019)
Accurately determining the orientation of borehole sensors is of paramount importance for microseismic monitoring applications. We calculate the relative bearing angle that allows the orientation of borehole receivers for microseismic monitoring by means of an energy-based strategy that considers the recorded horizontal amplitudes of a perforation shot of known position. This process also allows the appropriate separation of P and S waves, enhancing the accuracy of further processing steps (e.g. time arrival picking). By taking into account the inclination and azimuth of the well, this approach searches for the angle that, after the proper rotations are applied, leads to maximum energy in the source–receiver direction (and minimum energy in the transverse direction). We test the method on synthetic records and two field datasets from Vaca Muerta Formation (Neuquina Basin, Argentina) and statistically evaluate its sensitivity to noise and picking errors. The results show that, in spite of its simplicity, the proposed method is a robust approach that leads to reliable bearing angle estimates with minimum user supervision.